Development of an Expert System for Predicting the Effects of Economic Activities on Groundwater Quality - Mongkon, Ta-Oun (2000)
Presently, groundwater conservation has become a very important issue in the world. The attention has been given to groundwater pollution problems. The application of Information Technology (IT) in the form of an expert system namely GWPES (Groundwater Pollution Expert System) will be able to help in information retrieval and decision support when dealing with groundwater pollution and protection. The rule base and Graphic User Interface (GUI) of GWPES was developed using wxCLIPS version 1.62 for Personal Computer (PC), version 1.49 for Local Area Network (LAN) system and Authorware 3.5 for developing graphic presentation files. These application softwares also supported the GWPES for the interpretation of some knowledge data bases. The wxCLIPS expert system shell was originally designed by NASA (National Aeronautics and Space Administration). The rules were developed according to the comprehensive groundwater pollution information and Environmental Impact Assessment (EIA) procedure. The main menu of GWPES consists of six main parts as follows; Introduction, EIA Procedure, Concept, Prediction, Mitigation and Monitoring. The first three parts help all interested people related to EIA to understand groundwater pollution information and EIA procedure. The next three main parts have been incorporated into an expert system to predict future situation of groundwater [Pollution Vulnerability, Nitrogen Fertiliser Impact and Project Activities Impact], and to propose possible mitigation measures as well as to approach groundwater quality-monitoring plan. Knowledge bases for GWPES have been elicited from domain experts (2 geologists, 1 hydrologist, 1 civil engineering majoring in groundwater, 2 soil scientists and 1 soil & water engineering expert) through interviews, existing established literature, EIA reports and field study. The GWPES has friendly graphical user interface that has been accepted satisfactorily by external domain experts and end-users.